2017
DOI: 10.1590/1516-3180.2016.0350240317
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus in cystic fibrosis patients: do we need to care? A cohort study

Abstract: CONTEXT AND OBJECTIVE: The prevalence of a variety of potentially pathogenic microorganisms in cystic fibrosis patients, such as methicillin-resistant Staphylococcus aureus (MRSA), has increased over the past decade. Given the increasing prevalence of MRSA and the few data available in the literature, better understanding of the clinical repercussions of colonization by this bacterium in cystic fibrosis patients becomes essential. This study aimed to evaluate the repercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
9
0
4
Order By: Relevance
“…Staphylococcus aureus is one of the earliest and most prevalent pathogens isolated from the airways of CF patients. Colonisation with methicillin-resistant S. aureus (MRSA) has risen dramatically over the past decade [2] and has been associated with poor clinical outcomes in these patients [3]. According to the Brazilian Cystic Fibrosis Registry 2017, MRSA was the seventh most common microorganism isolated from respiratory cultures of CF patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is one of the earliest and most prevalent pathogens isolated from the airways of CF patients. Colonisation with methicillin-resistant S. aureus (MRSA) has risen dramatically over the past decade [2] and has been associated with poor clinical outcomes in these patients [3]. According to the Brazilian Cystic Fibrosis Registry 2017, MRSA was the seventh most common microorganism isolated from respiratory cultures of CF patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…These authors speculated that the absence of an association between early P. aeruginosa infection and abnormal subsequent chest CT findings may be attributed to aggressive treatment. Other studies including adolescent or older patients chronically colonized with methicillin-resistant Staphylococcus aureus or P. aeruginosa identified increased total modified Bhalla scores, reflecting the presence of structural lung disease (14,15). Another study on the isolation of proinflammatory pathogens ( P. aeruginosa , Streptococcus pneumoniae and Aspergillus species) in bronchoalveolar lavage fluid showed a relationship between infection status with these pathogens and CT findings in infants (29).…”
Section: Discussionmentioning
confidence: 99%
“…The total score could range from zero (absence of abnormalities) to 37 (all abnormalities present and severe). The modified Bhalla score was previously validated in CF patients in another study at this institution (14) and was subsequently established not only for clinical studies but also for patient follow-up (15,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an emerging consensus that MRSA is an important pathogen in CF rather than simply a marker of severe disease 37 *. A recent case control study from Brazil 38 has shown that patients infected with MRSA have a greater respiratory impairment at the time of chronic infection and disease progression is more rapid in patients with MRSA compared to those with sensitive strains of S. aureus. CF patients with MRSA have also been shown to have worse CT appearances than those who are free of infection 39 .…”
Section: Formatted: Font: Italicmentioning
confidence: 99%